ARDUINO UNO-BASED TODDLER STUNTING DETECTION TOOL USING A MOBILE APPLICATION - Sri Restu Ningsih; Ade Irma Suryani; M. Tasnim; Elizamiharti Elizamiharti; Sotar Sotar; Erdisna Erdisna (JOISIE (Journal Of Information Systems And Informatics Engineering), 2026)
The high prevalence of stunting in West Sumatra Province, especially in Padang City, is currently a serious problem. According to the Padang City Health Office, there were 1,569 children detected with stunting in 2024. The current problem is that stunting examinations are still carried out manually at health centers, and there is no system that can detect stunting quickly and accurately. This problem became the focus of researchers in innovating the design of a stunting detection application for toddlers. The purpose of this study is to design and build a stunting detection application for toddlers based on Arduino Uno using a mobile application, so that stunting in toddlers can be detected quickly, accurately, and validly. The system development method used is the Research and Development (R&D) method with a 4-D model approach (Define, Design, Development, and Disseminate), which is a research and development method used to produce a product in the form of a model that requires various tests for product effectiveness. The result of this study is a technological innovation in the form of a stunting detection tool and system that can automatically detect stunting in toddlers validly and accurately using a mobile application. This system can predict stunting status with high levels of accuracy, precision, and recall.